Human granzyme B regulatory B cells prevent effector CD4+CD25- T cell proliferation through a mechanism dependent from lymphotoxin alpha - Sailliet, Nicolas; Mai, Hoa-Le; Dupuy, Amandine; Tilly, Gaëlle; Fourgeux, Cynthia; Braud, Martin; Giral, Magali; Robert, Jean-Michel; Degauque, Nicolas; Danger, Richard; Poschmann, Jeremie; Brouard, Sophie (Frontiers in Immunology, 2023)
Human Granzyme B (GZMB) regulatory B cells (Bregs) have suppressive properties on CD4+ effector T cells by a mechanism partially dependent on GZMB. Moreover, these cells may be easily induced in vitro making them interesting for cell therapy. Herein we characterize this population using single cell transcriptomics. We find that Bregs exhibit a unique set of 149 genes differentially expressed and which are implicated in proliferation, apoptosis, metabolism, and altered antigen presentation capacity consistent with their differentiated B cells profile. To investigate their regulatory properties, Bregs or total B cells were co-cultured with T cells and gene expression analysis was used to identify receptor ligand interactions and to reveal gene expression changes in the T cells. Notably, Bregs induced a strong inhibition of T cell genes associated to proliferation, activation, inflammation and apoptosis compared to total B cells. We identified and validated 5 receptor/ligand interactions between Bregs and T cells. Functional analysis using specific inhibitors was used to test their suppressive properties and we identified Lymphotoxin alpha (LTA) as a new and potent Breg ligand implicated in Breg suppressive properties. These results are the first demonstration on the role of LTA in the suppressive properties of Bregs.